2022
DOI: 10.3390/foods11182720
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication and Characterization of W/O/W Emulgels by Sipunculus nudus Salt-Soluble Proteins: Co-Encapsulation of Vitamin C and β-Carotene

Abstract: W/O/W emulsions can be used to encapsulate both hydrophobic and hydrophilic bioactive as nutritional products. However, studies on protein stabilized gel-like W/O/W emulsions have rarely been reported, compared to the liquid state multiple emulsions. The purpose of this study was to investigate the effect of different oil–water ratios on the stability of W/O/W emulgels fabricated with salt-soluble proteins (SSPs) of Sipunculus nudus. The physical stability, structural characteristics, rheological properties, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…This could be because the free probiotics are largely inactivated when passing through the gastrointestinal tract and thus cannot exert a beneficial biological regulation effect. 25 The results also showed that fish oil had little effect on colon length in UC mice. This was possibly due to the relatively low content of fish oil used, with each mouse (26 g weight) ingesting only around 7 μL of fish oil every day.…”
Section: Resultsmentioning
confidence: 93%
See 3 more Smart Citations
“…This could be because the free probiotics are largely inactivated when passing through the gastrointestinal tract and thus cannot exert a beneficial biological regulation effect. 25 The results also showed that fish oil had little effect on colon length in UC mice. This was possibly due to the relatively low content of fish oil used, with each mouse (26 g weight) ingesting only around 7 μL of fish oil every day.…”
Section: Resultsmentioning
confidence: 93%
“…Additionally, the presence of fish oil may enhance the adhesion of the probiotics within the colon, making it easier for them to attach to the intestinal wall, thereby providing a more stable foundation for probiotic action. 25…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…DE is an appropriate carrier for micronutrients that, in addition to protecting them against degradation, provides the possibility of co-encapsulation of both hydrophilic and hydrophobic compounds to produce enhanced health benefits [13], as evidenced in Table 1. In this context, Dai et al [14] co-encapsulated vitamin C and β-carotene within the W 1 and oil phase of a DE, respectively; stabilized by different concentrations of Sipunculus nudus salt-soluble proteins. The values of encapsulation efficiency (EE) for vitamin C at 1% and 2% of protein concentrations were 87.3% and 91.2%, respectively.…”
Section: Food Applications Of W 1 /O/w 2 Des 21 Fortification Purposesmentioning
confidence: 99%